LoRa performance testing experiment - Zhang, Tongshuo (2018)
This article introduces LoRa using comparisons with other wireless standards to point out the advantages. Also, an experimental project about regulation of loRa performance will be introduced. The purpose of this project is to understand the impact of LoRa’s inner factors on long-range data transmission performance. There are three settings we will control to get transmission performance index at different transmission distances in Singapore. There are three major steps in this project shown below: 1. Selection of the experiment’s receiving and transmitting points.; 2. Collection of performance data at different distances by transmitting and receiving data with different settings of the three variables.; 3. Analysis on the performance results to find the correlation between the settings and the performance.